The Mindfulness and Husband Support Overcome Kim’s Suffering In Kim Ji Young Born:1982 Movie (2019) - Nurhasanah, Tia; Isminarni, Siri; Ramadhina, Retno (STIBA IEC JAKARTA, 2025)
This research discusses the psychological condition experienced by Kim Ji Young and how her husband's role in supporting her mental recovery process. This research uses three theories, namely Cognitive Theory by Aaron T. Beck, Emotional Support Theory by Shelley E. Taylor, and Theory of Personal Growth by Abraham Maslow. The method used is a qualitative descriptive approach, by analyzing several important scenes in the film Kim Ji Young: Born 1982. The results show that Kim experiences great inner pressure because she must carry out many roles at once as a mother, wife, and daughter-in-law, but does not get enough emotional support. This makes Kim feel depressed, confused, and sometimes even feel that she cannot control herself or does not recognize what she is doing. In addition, Kim also often blames herself and imagines bad things that are not necessarily happening. On the other hand, her husband tries to be a good listener, give her space, and keep learning to be better. Although not perfect, he seems to have the intention and effort to grow with Kim. This research shows that in domestic relationships, a sense of security and emotional support is very important so that each of us can develop and be mentally healthy.